Perceptions and practices of psychologists experts in the field of domestic and family violence against women (Research, Society and Development, 2024)
This study aimed to investigate how the practices that psychologists experts develop in the field of domestic and family violence against women are characterized and which are the perceptions they present about their performance. This is a qualitative, cross-sectional and exploratory research. The participants were six psychologists experts who work in Courts of Domestic and Family Violence against Women in the state of Rio Grande do Sul in Brazil. Semistructured interviews were performed and analyzed using content analysis. The results indicate that the professionals have conceptions in line with the literature on the repercussions of gender roles in the phenomenon of violence against women. However, they consider that the cyclical dynamics of this phenomenon has secondary importance, favoring individual issues of those involved in the situation of violence for the understanding of the cases. The psychologists' previous experiences seem to contribute to qualify their expert performance. On the other hand, a lack of convergence was found among the participants about the knowledge that underlies their practical. Judicial determinations for assessment usually occur during the implementation of urgent protective measures and predominantly involve the evaluation of male perpetrators of violence. The interview was referred to as the main evaluative procedure used in the assessments. Finally, while the intersectoral actions articulated with the service network for women seem promising, the care for men remains challenging. The findings of this study provide contributions on theoretical and technical aspects that can be prioritized in training that seeks to qualify the psychological assessments carried out in this area.